2016
DOI: 10.1080/16066359.2016.1239081
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of alcohol consumption by timeline follow back vs.smartphone-based daily interviews

Abstract: This study compared alcohol consumption data collected through daily interviews on a smartphone with data collected via the Timeline Follow-Back (TLFB) during a 6-week pilot study of a smartphone-based alcohol intervention system. The focus of the study was to assess for discrepancies between the two measurement methodologies on commonly utilized alcohol outcome variables. Twenty-five participants between 22 and 45 years of age and were drinking heavily at study incipience completed a 6-week alcohol interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 39 publications
2
62
1
4
Order By: Relevance
“…Substance use is a discrete episodic behaviour, influenced by immediate environmental factors (e.g. For example, Monk et al [14] demonstrated that a greater number of alcoholic drinks were reported in real time using EMA than when assessed retrospectively (see also [15]). Furthermore, the assessment of substance use and its correlates in the laboratory often relies on retrospective recall which can be biased, particularly when measured following periods of drug/alcohol intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use is a discrete episodic behaviour, influenced by immediate environmental factors (e.g. For example, Monk et al [14] demonstrated that a greater number of alcoholic drinks were reported in real time using EMA than when assessed retrospectively (see also [15]). Furthermore, the assessment of substance use and its correlates in the laboratory often relies on retrospective recall which can be biased, particularly when measured following periods of drug/alcohol intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…Inherent in this methodology is the reliance on patients’ recall of their alcohol intake. While it is remarkable how precise some patients can be about alcohol intake, particularly among those with severe dependence where alcohol is central to their life, relying on retrospective data necessarily becomes less effective as one asks people to report events over longer time periods [22]. In addition, interviewing patients about events prior to admission introduces the possibility of recall bias as individuals try to explain their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Results can be crosschecked with other measures of alcohol consumption such as the AUDIT and with prospective approaches to collection of alcohol consumption data. Such comparisons have generally showed that the TLFB is consistent with both and can be used interchangeably with prospective diaries, interactive voice response phone messaging (IVR) or the AUDIT (5154). The TLFB procedure is time consuming, however, as it requires considerable probing to ensure that recall is as accurate as possible over each day during the 30, 60 or 90 day recall period.…”
Section: Introductionmentioning
confidence: 99%